Pengaruh Persepsi Kemudahan Mobile Banking, Kepercayaan Nasabah, Dan Citra Lembaga Terhadap Minat Menabung Generasi Muda Pada Bank Jateng Syariah - Meilisa Sekar Langit; Fadli Hudaya (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to examine the relationship between perceived ease of use of mobile banking, customer trust, and corporate image and Generation Z’s saving intention at Bank Jateng Syariah. A quantitative survei was conducted involving 120 respondents selected trough purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regresion. The results show that perceived ease of use of mobile banking and customer trust are positively and significantly associated with saving intention, whereas corporate image is not significantly associated with saving intention. Simultaneously, the three variables are significantly related to saving intention, with and Adjusted R Square of 0,644. These findings indicate that, for Generation Z, the ease of using digital banking services and trust in the bank are more closely associated with saving inton than corporate image.